A new crystallization pattern of nested tetrahedral lamellar structure for the face-centered cubic metals with low stacking fault energy. (September 2020) - Wu, Yongquan; Zhou, Tao; Yu, Ronggang; Lai, Qinmei; Wang, Hao; You, Jinglin
Abstract: It's well known that the lamellar (LAM) and five-fold-twinning (FFT) structures are two primary patterns during the early crystallization stage of FCC (face-centered cubic) metals. In this letter, we add a new third one, i.e. a nested tetrahedral lamellar (NTL) structure. In common with LAM and FFT, NTL is also a mixture of FCC and HCP (hexagonal close-packed). Differently, NTL has four tetrahedral growth orientations corresponding to four cellular bulges and a central core of tetrahedral shells nested one-by-one. This NTL acts also as the precursor of FFT and it has great differences in growth morphology and kinetics with LAM. Graphical abstract: Image, graphical abstract